Pharmacokinetic and Pharmacodynamic Bio‐Similarity of ADL‐018 to Innovator Omalizumab: A Randomized Study in Healthy Adults - Sunil Soitawala; Hiren Prajapati; Hiren Mehta; Pawan Kumar Singh (Clinical Pharmacology in Drug Development, 2026)
Abstract Bioequivalence and safety of ADL‐018, an omalizumab biosimilar, were compared with United States‐licensed omalizumab (US‐OMA) and European Union‐approved omalizumab (EU‐OMA), both approved for allergies. Healthy adults were randomized (1:1:1) to receive a dose of ADL‐018, US‐OMA, or EU‐OMA (150 mg/mL). Pharmacokinetic (PK) parameters, including AUC (0–last) , AUC (0–∞) , and C max , were considered equivalent if 90% CIs of geometric mean ratios (GMRs) were within predefined equivalence margin (0.80–1.25) using ANCOVA model. Other PK parameters, pharmacodynamics (PD) (free/total immunoglobulin E [IgE]), immunogenicity, and safety were compared. Overall, 306 participants (n = 102 per arm) were dosed; 287 completed the study. Equivalence of primary PK parameters was confirmed for pairwise comparisons, with 90% CIs within the predefined margin (GMRs of ADL‐018 vs US‐OMA: AUC (0–last) —1.08, AUC (0–∞) —1.07, C max —1.05; GMRs of ADL‐018 vs EU‐OMA: AUC (0–last) —1.06, AUC (0–∞) —1.06, C max – 1.05; and GMRs of US‐OMA vs EU‐OMA: AUC (0–last) —0.99, AUC (0–∞) —0.99, C max —1.00). PK/PD parameters were comparable across arms. Increase in total IgE (AUEC ∼30,000 to 35,000 h IU/mL) and decrease in free IgE (AUEC ∼29,000 to 35,000 h IU/mL) were comparable across arms. Similar incidence of adverse events across arms (treatment‐emergent adverse events: ADL‐018, n = 6; US‐OMA, n = 5; EU‐OMA, n = 4) was observed. ADL‐018 demonstrated PK/PD equivalence and comparable safety profile to reference omalizumab.